Schilddrüsenfunktionsstörungen in der Schwangerschaft - Hamza, Amr; Schlembach, Dietmar; Schild, Ralf Lothar; Groten, Tanja; Wölfle, Joachim; Battefeld, Wilgard; Kehl, Sven; Schneider, Michael (gynäkologische praxis, 2024)
With the onset of pregnancy, TSH values fall then rise with ongoing gestation. A TSH screening should be performed in the first trimester under certain indications. Furthermore, the TPO-Ab status should be determined when the TSH levels exceeds 2.5 mU/l as it might lower threshold of a levothyroxine (LT4) substitution. Subclinical hypothyroidism is associated with an increased risk of miscarriage, preterm birth but not an increased risk of preeclampsia, fetal growth restriction or adverse neonatal neurocognitive outcomes and may not require a supplementation especially with negative TPO-Ab. However, the overt hypothyroidism requires LT4 administration. A manifest hyperthyroidism necessitates treatment adjustments before and with the onset pregnancy. Propylthiouracil is recommended in the first trimester and replaced by with thiamazole in the second trimester. A thorough birth plan with neonatological management should be planned. In cases of a fetal hyperthyroidism, a vertical treatment should be introduced in perinatal centres with a specialized experience. Regarding birth management, a detailed intra- and postnatal management plan, including a specialized paediatric care, is necessary. Fetal hyperthyroidism should be ruled out prenatally upon taking thyrostatic agents during the first trimester. Intrauterine therapies for fetal hyper- and hypothyroidism should only be carried out after careful consideration in centres with a therapeutic expertise. In complex cases, the birth should occur in a prenatal centre with paediatric personal that have the necessary expertise.
CRIS-Team Scopus Importer:2024-08-23
Keywords: hyperthyroidism; hypothyroidism; thyroid disease; TSH